Magnetic-Water-Enhanced Tomato Yield and Antioxidant Response Under Arid Conditions of South Tunisia - Rawaa Akrimi; Mahmoud Mhamdi; Ghassen Abid; Hedyea Ezzeddine; Issam Nouiri (Horticulturae)
The current applied research evaluated the impact of magnetic water on agronomic and physiologic responses of tomatoes. The field experiment consisted of the irrigation of a 1000 m2 tomato plot with two water treatments (NMW = non-magnetized water; MW = magnetized water) and three tomato varieties (Dorra, Ercole, and Gladys). Biomass accumulation, yield, physicochemical quality traits, osmoticums, antioxidant enzymes, and the transcript level of defense-related genes were analyzed. Results showed that MW treatment showed 32%, 53%, and 57% yield increase in Dorra, Ercole, and Gladys, respectively. Dorra and Gladys were, respectively, the highest and the lowest yielding varieties. MW was effective in enhancing the irrigation water use efficiency (IWUE) and irrigation water productivity (IWP). Plants grown under MW had less catalase (CAT), guaiacol peroxidase (GPOX), super oxide dismutase (SOD), and ascorbate peroxidase (APX) activities, and hydrogen peroxide (H2O2) level. The reducedproline and soluble sugar content (SSC) accumulation in MW treatment indicate a reduced osmotic reaction. The upregulation of SlAPX in Gladys and SlSOD in Dorra and Ercole with MW had positive impacts on growth regulation and reduction in oxidative damage. The results clarified the roles of MW and its rule mechanisms in tomato, giving more theoretical foundation for physical water treatment in the agricultural sector.